The definitive guide to HR management tools (collection) - Davis, Alison (Alison Bonnie), 1957-; Shannon, Jane, 1943-; Cascio, Wayne F.; Boudreau, John W.; Director, Steven M.; Sesil, James C.; Biswas, Bashker, 1944-; Waber, Ben, 1984- (FTPress Delivers, 2013)
A brand new collection of high-value HR techniques, skills, strategies, and metrics ... now in a convenient e-format, at a great price! HR management for a new generation: 6 breakthrough eBooks help you help your people deliver more value on every metric that matters This unique 6 eBook package presents all the tools you need to tightly link HR strategy with business goals, systematically optimize the value of all your HR investments, and take your seat at the table where enterprise decisions are made. In The Definitive Guide to HR Communication: Engaging Employees in Benefits, Pay, and Performance, Alison Davis and Jane Shannon help you improve the effectiveness of every HR message you deliver. Learn how to treat employees as customers ... clarify their needs and motivations ... leverage the same strategies and tools your company uses to sell products and services ... package information for faster, better decision-making ... clearly explain benefits, pay, and policies ... improve recruiting, orientation, outplacement, and much more. In Investing in People, Second Edition, Wayne Cascio and John W. Boudreau help you use metrics to improve HR decision-making, optimize organizational effectiveness, and increase the value of strategic investments. You'll master powerful solutions for integrating HR with enterprise strategy and budgeting -- and for gaining commitment from business leaders outside HR. In Financial Analysis for HR Managers, Dr. Steven Director teaches the financial analysis skills you need to become a true strategic business partner, and get boardroom and CFO buy-in for your high-priority initiatives. Director covers everything HR pros need to formulate, model, and evaluate HR initiatives from a financial perspective. He walks through crucial financial issues associated with strategic talent management, offering cost-benefit analyses of HR and strategic financial initiatives, and even addressing issues related to total rewards programs. In Applying Advanced Analytics to HR Management Decisions, pioneering HR technology expert James C. Sesil shows how to use advanced analytics and "Big Data" to optimize decisions about performance management, strategy alignment, collaboration, workforce/succession planning, talent acquisition, career development, corporate learning, and more. You'll learn how to integrate business intelligence, ERP, Strategy Maps, Talent Management Suites, and advanced analytics -- and use them together to make far more robust choic ...